Respiratory Mucosal Immunity: Kinetics of Secretory Immunoglobulin A in Sputum and Throat Swabs From COVID-19 Patients and Vaccine Recipients - Ren, Cuiping; Gao, Yong; Zhang, Cong; Zhou, Chang; Hong, Ying; Qu, Mingsheng; Zhao, Zhirong; Du, Yinan; Yang, Li; Liu, Boyu; Wang, Siying; Han, Mingfeng; et al. (Frontiers in Microbiology, 2022)
While IgM and IgG response to SARS-CoV-2 has been extensively studied, relatively little is known about secretory IgA (sIgA) response in respiratory mucosa. Here we report IgA response to the SARS-CoV-2 in sputum, throat swabs, and serum with nucleocapsid protein (NP) enzyme-linked immunosorbent assays (ELISA) in a cohort of 28 COVID-19 patients and 55 vaccine recipients. The assays showed sIgA in respiratory mucosa could be detected on the first day after illness onset (AIO), and the median conversion time for sIgA in sputum, throat swabs, and serum was 3, 4, and 10 days, respectively. The positive rates of sIgA first week AIO were 100% (24/28) and 85.7% (24/28) in sputum and throat swabs, respectively, and were both 100% during the mid-onset (2–3 weeks AIO). During the recovery period, sIgA positive rates in sputum and throat swabs gradually decreased from 60.7% (17/28) and 57.1% (16/28) 1 month AIO and the sIgA antibodies were all undetectable 6 months AIO. However, serum IgA positive rate was still 100% at 4 months and 53.6% (15/28) at 6 months. Throat swabs obtained from volunteers who received inactivated SARS-CoV-2 vaccines by intramuscular delivery all showed negative results in IgA ELISA. These findings will likely improve our understanding of respiratory mucosal immunity of this emerging disease and help in containing the pandemic and developing vaccines.